(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Aim: Guatteria gaumeri has antioxidant, anti-inflammatory, and anti-diabetic activities. In the present randomized double-blind placebo-controlled trial is the efficacy of guatteria gaumeri mother tincture in hyperlipidemia. Hyperlipidemia patients meeting the inclusion criteria were randomly assigned to the treatment and placebo. Methods: 30 patients in the treatment group took guatteria gaumeri mother tincture; whereas the patients in the placebo group took placebo mother tincture for 12 weeks. The lipid profiles of the patients were evaluated at baseline, and after 6 and 12 weeks of the clinical trial. Results: The final results showed that guatteria gaumeri mother tincture significantly p-value 0.05 and improved LDL, HDL, cholesterol, compared to the placebo group. The guatteria gaumeri showed an inhibitory effect on hepatic enzymes and possible liver toxicity. No serious side effect was reported for guatteria gaumeri mother tincture administration. Therefore, guatteria gaumeri mother tincture could be considered as a supplement for the treatment of dyslipidemia.